Economic effects of reorganising an agro-food supply chain: some evidence from Poland. Issue 5 (10th August 2015) - Falkowski, Jan
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Much has been said about the nature of the agro-food supply chain. Yet, the consequences of reforming supply chain institutions have less often been studied, especially from an empirical perspective. The purpose of this paper is to examine the economic consequences of a radical reorganisation of the system of exchange in the agro-food sector in Central and Eastern Europe, during the process of transition from a centrally planned economy to a market economy. By considering a historical example from the dairy sector in Poland, the author provides evidence that the disorganisation of vertical linkages between upstream and downstream producers can be very costly. The most conservative estimates suggest that the dislocation of inter-firm relationships accounted for approximately 20 per cent of the drop in milk production observed in the early-transition phase in question. Design/methodology/approach – The empirical approach is based on econometric analyses. The empirical strategy the author adopts is similar in spirit to a standard difference-in-differences method. More specifically, to study the outcomes of the disruptions in supply chain the author adopts an event-study approach. Thus, the author compares the relative changes in milk production in the post-treatment period relative to pre-treatment period between regions more or less exposed to disruptions to supply chain. Findings – The most conservative estimates suggest that the dislocation to inter-firm relationships accounted for approximately 20 per cent of the fall in milk production observed in the early-transition phase. Originality/value – Two key features distinguish the approach from the previous studies. First, through the use of a more direct measure of problems affecting vertical relationships between farmers and processors the author has access to higher quality proxies for the supply chain disruptions. To this end, the author focuses on the dislocation to milk procurement system that arose in the very early phase of transition, manifesting itself in the break up of vertical linkages between farmers and dairy industry. Second, in contrast to the existing studies which exploit variation between transition countries, the author focus on within-country evidence. To best of the author knowledge, this paper is the first to investigate agricultural output during transition using within country variation.